Assessment of Brown Algae (Phaeophyceae) and Sediment Collected from Sanur Coastal Waters Based on Bioaccumulation Factors and Human Health Risks Related to Microplastic Ingestion Exposure - I Made Gde Sudyadnyana Sandhika; Putu Angga Wiradana; I Gede Widhiantara; I Wayan Rosiana; Anak Agung Ayu Putri Permatasari; Ni Kadek Yunita Sari; Emanuel Maramba Hamu; Agoes Soegianto; Bambang Yulianto (Universitas Gadjah Mada, 2023)
This study aimed to analyze Microplastics (MPs) contamination in brown algae and sediments, and their bioaccumulation factors, and estimate the risk to human health associated with exposure to ingested MPs collected from the water of the Sanur Beach, Bali Province. The samples were collected from three beaches which were determined using a purposive sampling method. The mean number of MPs found in P. australis was the same on all beaches, namely 17 items/seaweed, higher than S. aquifolium on all beaches. Line-shaped MPs were dominantly found in all algae (98.76%). A high percentage of line-shaped MPs was found in sediments at Mertasari and Semawang Beaches, but not at Sindhu Beach. The highest mean size of MPs in algae was found in P. australis at Semawang Beach, and sediments at Mertasari beach. The highest concentrations of MPs were also found in P. australis on the three coasts. The BAF value showed that the absorption of MPs in the sediment to brown algae was still low (<1). Values related to intake of brown algae consumption ranged from 190.58-1429.41 MPs item/week adjusted for calculation recommendations.